2022
DOI: 10.1186/s40795-022-00646-0
|View full text |Cite
|
Sign up to set email alerts
|

Key predictors of undernutrition among children 6–59 months in the Buea Health District of the Southwest region of Cameroon: a cross sectional community-based survey

Abstract: Background According to the 2018 Demographic and Health Survey, undernutrition remains a public health problem among Cameroonian children under-five. This varies across the country, greatest in areas with ongoing humanitarian crisis, such as the Southwest region. However, data on the burden of undernutrition in the Southwest region is sparse. This study aimed to assess the prevalence and predictors of undernutrition among children under-five in the Buea health district of the Southwest region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Male children were nearly twice as likely as female children to be undernourished. This nding aligns with the results of previous research that has consistently shown that boys are at a greater risk of undernutrition than girls are during con ict, with some studies in Buea Cameroon and a meta-analysis indicating that this risk is twice as high (15,16). This gender disparity is particularly pronounced in some regions, such as rural China (17).…”
Section: Discussionsupporting
confidence: 90%
“…Male children were nearly twice as likely as female children to be undernourished. This nding aligns with the results of previous research that has consistently shown that boys are at a greater risk of undernutrition than girls are during con ict, with some studies in Buea Cameroon and a meta-analysis indicating that this risk is twice as high (15,16). This gender disparity is particularly pronounced in some regions, such as rural China (17).…”
Section: Discussionsupporting
confidence: 90%